REASONABLENESS OF THE EUROPEAN UNION TAX LAW - HAVRYLYUK, RUSLANA; PATSURKIVSKYY, PETRO (Ehrlich's Journal, 2024)
The relevance of the study of the reasonableness of the European Union tax law is due to the cotroversion of the previously obtained results of its cognition in the European tax law doctrine, and also due to the practical challenges Ukraine faces in the field of European tax law in connection with the beginning of practical implementation of its constitutionally determined strategy for obtaining membership in the European Union. The study is based on the hypothesis that the reasonableness of EU tax law is complex. The methodology for testing this hypothesis involves solving the following tasks: 1) to reveal fiscal democracy as a manifestation of the reasonableness of EU tax law; 2) to analyse the essence of legal certainty of EU tax legislation as evidence of its reasonableness; 3) to study the prohibition of abuse of EU tax rights by subjects of tax legal relations as a component of its reasonableness. The aforementioned methods of testing the main hypothesis of the study are based on the anthroposociocultural approach to the knowledge of tax law. It is established that the key criterion for determining the degree of reasonableness of the EU tax law is the degree of its compliance with the dual human nature. The EU tax law also combines private law and public law substance. The property of reasonableness of EU tax law is an integral phenomenon that includes different layers of legal matter. They include legitimate ways of establishing this right, its implementation in the most difficult conditions of various tax and legal regimes, protection of this right from its deformation due to arbitrary behaviour of subjects of tax relations and measures of tax and legal liability for violation of its provisions. The EU Court of Justice is the fundamental guarantor of the reasonableness of the EU tax law. It is the Court of Justice that ensures the legal certainty of EU tax legislation.